(untitled) (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2026)
This study examines the influence of moral culture, discipline, and core competencies on employee productivity at PT Pos Indonesia, Semarang Branch. The moral culture, encompassing values such as trustworthiness, competence, harmony, loyalty, adaptability, and collaboration, is a crucial element in enhancing employee productivity. Additionally, work discipline plays a significant role in creating a conducive work environment to achieve organizational goals. Core competencies, including skills and knowledge, are considered key factors in producing optimal job performance. Using multiple linear regression analysis, the study finds that these three variables positively impact employee productivity. This research is expected to provide insights for companies to improve employee performance by strengthening organizational culture, work discipline, and employee competency development.